Mechanisms of autophagy and their implications in dermatological disorders - Xue, Shenghao; Lin, Yumeng; Chen, Haoran; Yang, Zhengyu; Zha, Junting; Jiang, Xuan; Han, Zhongyu; Wang, Ke (Frontiers in Immunology, 2024)
Autophagy is a highly conserved cellular self-digestive process that underlies the maintenance of cellular homeostasis. Autophagy is classified into three types: macrophage, chaperone-mediated autophagy (CMA) and microphagy, which maintain cellular homeostasis through different mechanisms. Altered autophagy regulation affects the progression of various skin diseases, including psoriasis (PA), systemic lupus erythematosus (SLE), vitiligo, atopic dermatitis (AD), alopecia areata (AA) and systemic sclerosis (SSc). In this review, we review the existing literature focusing on three mechanisms of autophagy, namely macrophage, chaperone-mediated autophagy and microphagy, as well as the roles of autophagy in the above six dermatological disorders in order to aid in further studies in the future.